Cuarenta años no son nada: ¿La reposición del clivaje autoritarismo-democracia en el sistema de partidos chileno? - Aubry, Marcel; Dockendorff, Andrés (Revista de Sociología, 2015)
On the occasion of the commemoration of the 40th anniversary of the breakdown of democracy in Chile, a sequence of events illustrates a possible replacement of the political cleavage or the authoritarianism-democracy division in the Chilean party system. This essay is part of an alternative line of argument to the hypothesis that emphasize the search for social structural differences as the basis of the alignments of the party system, centered around the classical model of Lipset and Rokkan (1967). Here the full cleavage model of Deegan-Krause (2008) is used, which dissects the cleavages and their possible combinations in three dimensions: socio-structural, normative and organizationalinstitucional. From the above, the article provides plausibility to the hypothesis that the replacement of the division authoritarianism/democracy is given in at least two elements of what constitutes a full cleavage: in the ideological alignments and in the organization of the party system. Given this, the decisive role of political agency placed on party élites to keep alive these kind of conflicts is proved. This is consistent with what was proposed a decade ago by Torcal and Mainwaring (2003). As for the comparative implications of the application of the theory of social cleavages to the Chilean case, the potential problem of giving it a general scope is observed, leaving the question about the relevance of using these concepts in the Latin American reality in an uncritical way.